Dampak Media Sosial terhadap Religiusitas Mahasiswa Universitas Negeri Jakarta - Julia Rizqi Rahmawati; Dela Ayu Puspita; Muhammad Zikri Azis; Abdul Fadhil (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
This study aims to examine the impact of social media on the religiosity of students at Universitas Negeri Jakarta (UNJ), focusing on both the positive and negative effects, as well as the factors influencing these outcomes. The research employs a descriptive qualitative method, relying on literature review and data collection through observations of social media use in students' religious activities. The findings indicate that social media can strengthen religiosity by providing access to religious content, forming religious communities, and enhancing religious knowledge. However, challenges such as the spread of hoaxes and the diversion of attention from worship also exist. In conclusion, careful management of social media is essential to maximize its positive impact on students' religiosity. The study recommends improving digital religious literacy, critical religious education, and guidance in social media use.